A new middle Cambrian bradoriid arthropod from Greenland and western Canada. (9th March 2015) - Peel, John S.; Streng, Michael
Abstract: Circum-Laurentian middle Cambrian (Cambrian Series 3) deposits in Greenland and British Columbia yield a new hipponicharionid bradoriid arthropod, Flumenoglacies n. gen., characterized by a comarginal, ramp-like structure which is crested by a continuous lobe. The narrow lobe is the result of the medial fusion of anterior and posterior lobes, seemingly a recurrent theme in hipponicharionid evolution. The type species, F . groenlandica n. sp., is described from the Ekspedition Brae Formation (Drumian Stage) of Peary Land but the description of two unnamed species from slightly older middle Cambrian strata of the Stephen Formation of British Columbia provides additional evidence for the wide distribution of Small Shelly Faunas during the Cambrian.